Teen pregnancy among sexual minority women: Results from the National Longitudinal Study of Adolescent to Adult Health - Goldberg, Shoshana K (J Adolesc Health, 2016)
PURPOSE: To explore the association between sexual orientation and teen pregnancy (before age 20) in a U.S. nationally representative cohort of young adult females aged 24–32. METHODS: 5,972 participants in Waves I and IV of the National Longitudinal Study of Adolescent to Adult Health were included. Self-reported sexual orientation identity was categorized as heterosexual, and three sexual minority [SM] groups: mostly heterosexual; bisexual; and lesbian [combining ‘mostly homosexual’ & ‘100% homosexual’]. Stepwise multivariate logistic regression models were fit to compare odds of teen pregnancy, and timing of teen pregnancy, between heterosexual and sexual minority [SM] groups, adjusting for sociodemographic characteristics, sexual victimization history, and sexual risk behaviors. RESULTS: After adjusting for sociodemographics and sexual victimization, bisexual women had significantly higher odds than heterosexual peers of teen pregnancy (OR=1.70; 95% CI=1.05, 2.75); this association was marginally significant after adjusting for sexual risk behaviors. Bisexuals were also more likely to have an early (before age 18) teen pregnancy (OR=2.04; 95% CI=1.17, 3.56). In contrast, lesbian women were significantly less likely to have a teen pregnancy than heterosexual (OR=0.47; 95% CI=0.23, 0.97), mostly heterosexual (OR=0.46; 95% CI=0.21, 0.99), and bisexual (OR=0.29; 95% CI=0.12, 0.71) women in final models. CONCLUSIONS: Expanding upon extant literature, we found opposing risk patterns for teen pregnancy between bisexual and lesbian women, likely due to distinct patterns of sexual risk taking. Findings suggest that SM-inclusive teen pregnancy prevention efforts tailored to meet the unique needs of SM young women, particularly bisexuals, are needed.